2023
DOI: 10.1039/d2gc04652k
|View full text |Cite
|
Sign up to set email alerts
|

Metal hydroxide assisted integrated direct air capture and conversion to methane with Ni/Al2O3catalysts

Abstract: An innovative integrated route for CO2 capture and conversion to methane relying on inexpensive metal hydroxides and nickel-based catalysts is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…In a previous report, with a 25 %Ni/Al 2 O 3 catalyst, temperature played a significant role as the catalysis was greatly hindered at temperatures below 225 °C. [37] With the 5 %Ru/Al 2 O 3 catalyst in the present study the difference in yield between 200 °C and 225 °C was rather minute (Figure 3a). 200 °C produced 19 % methane with a productivity of 101.6 g methane • h À 1 • kg cat À 1 .…”
Section: Resultsmentioning
confidence: 50%
See 3 more Smart Citations
“…In a previous report, with a 25 %Ni/Al 2 O 3 catalyst, temperature played a significant role as the catalysis was greatly hindered at temperatures below 225 °C. [37] With the 5 %Ru/Al 2 O 3 catalyst in the present study the difference in yield between 200 °C and 225 °C was rather minute (Figure 3a). 200 °C produced 19 % methane with a productivity of 101.6 g methane • h À 1 • kg cat À 1 .…”
Section: Resultsmentioning
confidence: 50%
“…Metal hydroxide salts have been shown to be efficient bases for the capture of CO 2 from the atmosphere. [21,37,65,66] Thus, we performed an air capture with 10 mmol of potassium hydroxide in water. The air capture produced 5 mmol of K 2 CO 3 as shown in the 13 C NMR spectrum in Figure S13.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prakash et al has recently shown that both sodium carbonate, sodium bicarbonate as well as other alkali metal carbonates in aqueous solution could be hydrogenated to methane using a nickel-based catalyst (25% Ni/Al 2 O 3 ). 34 Following this report, the same catalyst was initially used to test the conversion of carbon dioxide captured with trisodium phosphate to methane at 200 °C under a hydrogen pressure of 50 bar. This experiment led to a poor methane yield of only 2.6% in 6 hours (Table 1), which was likely the result of phosphorous compounds acting as ligand and binding to the nickel-based catalyst, inhibiting its reactivity (Fig.…”
Section: Resultsmentioning
confidence: 99%